2021
DOI: 10.3389/fpsyg.2021.668344
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudo-Value Approach to Analyze the Semantic Similarity of the Speech of Children With and Without Autism Spectrum Disorder

Abstract: Conversational impairments are well known among people with autism spectrum disorder (ASD), but their measurement requires time-consuming manual annotation of language samples. Natural language processing (NLP) has shown promise in identifying semantic difficulties when compared to clinician-annotated reference transcripts. Our goal was to develop a novel measure of lexico-semantic similarity – based on recent work in natural language processing (NLP) and recent applications of pseudo-value analysis – which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In previous work, we have used NLP methodologies and established their ability to differentiate between diagnostic groups (Adams et al, 2021; MacFarlane et al, 2017; Salem et al, 2021; van Santen et al, 2013). Salem et al (2021) examined seven automated language measures (ALMs) and found them able to accurately classify already‐diagnosed children into ASD and non‐ASD groups even after controlling for age and IQ.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have used NLP methodologies and established their ability to differentiate between diagnostic groups (Adams et al, 2021; MacFarlane et al, 2017; Salem et al, 2021; van Santen et al, 2013). Salem et al (2021) examined seven automated language measures (ALMs) and found them able to accurately classify already‐diagnosed children into ASD and non‐ASD groups even after controlling for age and IQ.…”
Section: Introductionmentioning
confidence: 99%